2019
DOI: 10.1017/s1047951119002622
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricle segmental function in childhood cancer survivors using speckle-tracking echocardiography

Abstract: Aim:Anthracycline-associated cardiotoxicity in childhood cancer survivors may relate to global or segmental left ventricular abnormalities from associated thromboembolic events and myocardial microinfarcts. We characterized left ventricular segmental changes by two-dimensional speckle-tracking echocardiography in anthracycline-treated asymptomatic childhood cancer survivors.Methods and Results:Childhood cancer survivors’ echocardiograms with normal left ventricular fractional shortening >1 year after anthra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
1
19
2
Order By: Relevance
“…Unlike conventional LVSF and LVEF, which are limited to one plane, strain can be measured in three planes, providing a better determination of cardiac function. Previous studies provided evidence that strain abnormalities can be seen early despite preserved LVEF by conventional echo measures, identifying cardiac involvement in CCSs prior to the development of overt systolic dysfunction (43,(46)(47)(48)(49)(50)(51)(52)(53)(54). However, a more recent multicenter study of cardiac strain in a large cohort of pediatric CCSs found only mild differences in parameters of longitudinal strain between patients and healthy controls, with most CCSs (92.3%) having longitudinal strain values within the normal range.…”
Section: Speckle Tracking Imaging and 3d Echocardiographymentioning
confidence: 99%
“…Unlike conventional LVSF and LVEF, which are limited to one plane, strain can be measured in three planes, providing a better determination of cardiac function. Previous studies provided evidence that strain abnormalities can be seen early despite preserved LVEF by conventional echo measures, identifying cardiac involvement in CCSs prior to the development of overt systolic dysfunction (43,(46)(47)(48)(49)(50)(51)(52)(53)(54). However, a more recent multicenter study of cardiac strain in a large cohort of pediatric CCSs found only mild differences in parameters of longitudinal strain between patients and healthy controls, with most CCSs (92.3%) having longitudinal strain values within the normal range.…”
Section: Speckle Tracking Imaging and 3d Echocardiographymentioning
confidence: 99%
“…Significant reductions in LV longitudinal strain in subendocardial segments were observed after 3 cycles of chemotherapy, while conventional LV systolic and diastolic conventional parameters, as well as LVEF, were relatively spare (36). Other studies have reported that LV regional wall motion abnormalities are closely associated with the development of cancer therapy-related cardiac dysfunction in patients undergoing chemotherapy and may also be an important predictor of DIC (37)(38)(39)(40)(41). To the best of our knowledge, we are the first to use strain analysis to evaluate the cardioprotective effect of a natural highaltitude environment on DIC.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of anthracycline cardiotoxicity is increased because of improved new diagnostic methods and close followup periods (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). To detect cardiac damage, the diagnostic approach adopted was based mainly on the estimation of left ventricular ejection fraction (LVEF) or left ventricular fractional shortening (LVFS).…”
Section: Discussionmentioning
confidence: 99%
“…Çilsal et al (24) showed a deterioration in the LV longitudinal strain index with STE in pediatric patients with cancer receiving anthracycline treatment. Akam-Venkata et al (22) demonstrated that asymptomatic patients with anthracycline-treated childhood cancer with normal left ventricular fractional shortening had lower global longitudinal and circumferential strain, and left ventricular longitudinal strain was lower in the majority of the segments. Thus, they thought that anthracycline cardiotoxicity was more global than regional.…”
Section: Discussionmentioning
confidence: 99%